Lærerutdannerens digitale kompetanse - Rune Johan Krumsvik; Kariane Westrheim; Eva Sunde; Ketil Langørgen (Högre Utbildning, 2012)
This case study focuses on how three teacher educators attempt to enhance their digital competence by participating in the project “Teach As We Preach (TAWP)”. At a policy level in Norway, high priority is given to information and communication technology (ICT) through the new educational reform (Læreplan for Kunnskapsløftet [LK06]). The ICT density is high in school, with one laptop per student considered desirable - a goal that is accomplished in upper secondary school. The main obstacle, however, seems to be the lack of digital competence among both pre-service and in-service teachers. However, the new White Paper No. 11 enhances digital competence to the fifth basic competence in teacher education. The study aims to enhance our understanding of how teacher educators’ develop their digital competence as part of their digital didactics and the research question is: How can students’ feedback in- and after plenary lectures contribute to enhance teacher educator’s digital competence? The empirical analysis shows that the informants, despite thresholds and challenges, find the strategy applied in this project constructive with regards to their professional development within the field of digital competence.